Legal Protection for Foreign Investors in Investing Capital in the National Capital City - Fachrurazi, Ahmad Reza (Andalas Law Journal, 2023)
The relocation of Indonesia's national capital to East Kalimantan requires a lot of capital, including from foreign investors. To safeguard the success of this project, regulation and legal protection for foreign investors in IKN are important. This ensures legal certainty and trust for foreign investors participating in the project. This legal research is normative research with secondary data qualitative analysis using a statutory approach. Data sources involve primary, secondary, and non-legal materials. Data was collected through literature studies and online sources. The government has created a special regulation, namely Government Regulation (PP) No. 12 of 2023, which supports investment in the National Capital City (IKN). While it provides strong legal incentives and protection, it is important to regularly monitor the impact of this regulation, improve conformity with environmental standards, encourage partnerships with UMKM, and intensify international promotion. As well as engaging stakeholders and improving licensing transparency. Legal protection for foreign investors in IKN is well-regulated through the UU PM and bilateral investment agreements. In the face of global competition, the government needs to maintain investment policy stability, improve ease of doing business, consider sustainable practices, and create specific legal protection regulations to attract more foreign investment for sustainable economic growth.